Metformin restores the mitochondrial network and reverses mitochondrial dysfunction in Down syndrome cells. (13th January 2017) - Izzo, Antonella; Nitti, Maria; Mollo, Nunzia; Paladino, Simona; Procaccini, Claudio; Faicchia, Deriggio; Calì, Gaetano; Genesio, Rita; Bonfiglio, Ferdinando; Cicatiello, Rita; Polishchuk, Elena; Polishchuk, Roman; et al.
Abstract: Alterations in mitochondrial activity and morphology have been demonstrated in human cells and tissues from individuals with Down syndrome (DS), as well as in DS mouse models. An impaired activity of the transcriptional coactivator PGC-1α/PPARGC1A due to the overexpression of chromosome 21 genes, such as NRIP1/RIP140, has emerged as an underlying cause of mitochondrial dysfunction in DS. We tested the hypothesis that the activation of the PGC-1α pathway might indeed reverse this mitochondrial dysfunction. To this end, we investigated the effects of metformin, a PGC-1α- activating drug, on mitochondrial morphology and function in DS foetal fibroblasts. Metformin induced both the expression of PGC-1α and an augmentation of its activity, as demonstrated by the increased expression of target genes, strongly promoting mitochondrial biogenesis. Furthermore, metformin enhanced oxygen consumption, ATP production, and overall mitochondrial activity. Most interestingly, this treatment reversed the fragmentation of mitochondria observed in DS and induced the formation of a mitochondrial network with a branched and elongated tubular morphology. Concomitantly, cristae remodelling occurred and the alterations observed by electron microscopy were significantly reduced. We finally demonstrated that the expression of genes of the fission/fusion machinery, namely OPA1 and MFN2, was reduced in trisomic cells and increased by metformin treatment. These results indicate that metformin promotes the formation of a mitochondrial network and corrects the mitochondrial dysfunction in DS cells. We speculate that alterations in the mitochondrial dynamics can be relevant in the pathogenesis of DS and that metformin can efficiently counteract these alterations, thus exerting protective effects against DS-associated pathologies.